Learning English is benefit to the students easily to get job after end of their study from University in Timor-Leste and foreign countries - João da Silva; Aurea Elisabete A.F Amaral; Virgina Martins (Publikasi Indonesia, 2024)
This article is describing the result of Learning English has it benefit to the finalist students easily to get job after end of their study from University in Timor-Leste and foreign countries. The purpose of this writing to know and identify the result of the University students after they end of their academic study at the University in Timor-Leste and international organization companies in the foreign countries. The method of this research is qualitative and quantitative or mixed method approach to describe, count the result of the students’ capacity in enhancing the English language skills in the classroom. The characteristics of the students are measured with the evaluation and assessment test to identify highest capacity, medium, low, and lowest level of the skills. Some students are identified as: (i) talk too much, ask questions and has low capacity (ii) the students who has own behavior in stay calm and not talk much shows he or she is a good capacity (iii). The students who do not talk much he or she has normal capacity; (iv) the students who has own characteristic speak in high levels and good skills and knowledge present. This means that every personality of the students are not the same in getting the study activity in teaching and learning processes. The teachers as an educator must mostly use the digital library for affecting and influencing the students during they run their job as teaching staff in the classroom. This aim to help and support the students in getting the foreign language easily and reduce the manual teaching including grammar translation methods is more effective in teaching a foreign language.